Method for analyzing content of elements in quartz etching liquid
By simplifying the pre-treatment process of the element content analysis method in quartz etching liquid, and using ICP-OES and ICP-MS for measurement, the problem of complex content of impurity elements in high-purity quartz in the prior art is solved, and an efficient and simple analysis method is achieved, reducing the consumption of experimental equipment.
Patent Information
- Application Number
- CN202411671373.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-04-04
AI Technical Summary
When detecting the content of impurities in high-purity quartz, the prior art methods are complex, the detection height limit is strictly required, the experimental environment and the blank space of the vessel are strict, and the impurities in the enriched etching liquid are difficult to remove, resulting in high consumption of experimental equipment.
A method for analyzing element content in quartz etching solution is provided. Through quartz cleaning, etching blank sampling, etching solution sampling, and measuring SiO2 content and impurity element content in etching solution, ICP-OES and ICP-MS are used for measurement, which simplifies the pre-processing process and reduces the pre-processing time.
It is realized that the etching depth, SiO2 content and 8 impurity elements can be obtained through the same quartz etching liquid, which reduces the pre-treatment time, improves efficiency, and reduces the consumption of experimental equipment.
Smart Images

Figure CN119757319A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor manufacturing, relates to surface coating treatment of semiconductors or semiconductor manufacturing equipment and devices, and specifically relates to a method for analyzing element content in quartz etching solution. Background Art
[0002] With the rapid development of the semiconductor industry, high-purity quartz has become one of the key basic raw materials in many cutting-edge fields. High-purity quartz raw materials need to go through a series of purification processes to finally obtain high-purity quartz sand products that meet the target requirements of the semiconductor field. Therefore, the processing of high-purity quartz products has the characteristics of great influence of the properties of the original ore, high product purity requirements and susceptibility to contamination. Among them, impurity elements have a greater impact on the quality of high-purity quartz products. For example, if the alkali metal elements lithium (Li), sodium (Na) and potassium (K) are too high, it will cause quartz glass to become devitrified and deformed at high temperatures; if the transition metal elements iron (Fe), chromium (Cr) and copper (Cu) are too high, it will produce color spots or cause quartz to discolor at high temperatures, affecting the light transmittance and reducing the reliability and stability of the instrument.
[0003] At present, the wet etching method is often used to detect the content of impurity elements in high-purity quartz. That is, hydrofluoric acid (HF) is used to etch the surface of high-purity quartz at different depths, and a part of the etching solution is measured by inductively coupled plasma optical emission spectrometry (hereinafter referred to as ICP-OES). 2 The other part is evaporated to dryness to enrich the impurity elements in the vessel, and the vessel is extracted with a low concentration nitric acid solution. The extract is then used to determine the contents of eight impurity elements (lithium (Li), sodium (Na), magnesium (Mg), aluminum (Al), potassium (K), calcium (Ca), copper (Cu) and iron (Fe)) by inductively coupled plasma mass spectrometry (hereinafter referred to as ICP-MS). Since the detection limit of the eight impurity elements in this method is at the ng / g level, strict requirements are placed on the experimental environment and blank experimental vessels. At the same time, it is difficult to remove the impurity elements in the vessel for enriching the etching solution, resulting in a large consumption of experimental equipment. Therefore, it is of great significance to invent a method for the content of elements in quartz etching solution. Summary of the invention
[0004] The present invention aims to solve the above problems, improve the existing detection method, and provide a new method for analyzing the element content in quartz etching solution, so as to achieve the goal of obtaining the etching depth, etching solution SiO 2 content and the content of 8 impurity elements in the etching solution; at the same time, reduce the pre-treatment etching time.
[0005] The method for analyzing the element content in the quartz etching solution provided by the present invention mainly comprises the following steps: (A) quartz cleaning; (B) quartz etching blank sampling; (C) quartz etching solution sampling; (D) SiO2 in the etching solution 2(E) Measurement and calculation of impurity element content in etching solution.
[0006] The technical solutions adopted in each process are as follows:
[0007] The method for analyzing the element content in a quartz etching solution provided by the present invention comprises the following steps:
[0008] A. Quartz cleaning
[0009] Place a clean empty bucket made of materials that do not react with quartz in a clean room of Class 100 or above, put the quartz in it and add pure water. Let it stand for 2-5 minutes and then pour it out. Repeat the above operation several times; then clean it with 40-80KHz ultrasound and blow it dry with a high-pressure air gun.
[0010] Preferably, the empty barrel is made of a material selected from polytetrafluoroethylene (PTFE), polyethylene (PE) or polypropylene (PP);
[0011] The ultrasonic cleaning method is as follows: add 1 / 3 to 1 / 2 volume of ultrapure water to the PTFE, PE or PP barrel containing quartz, place it in an ultrasonic cleaner, the ultrasonic frequency is 40 to 80KHz, the ultrasonic cleaning time is 30 minutes, and then rinse with ultrapure water for 1 minute; repeat the above operation 2-3 times, and finally blow dry with nitrogen.
[0012] B. Quartz Etching Solution Blank Sampling
[0013] Place a clean perfluoroalkoxy resin PFA container in the sampling area of a clean room of Class 100 or above as a clean container, add 4%-10% HF solution, leave it at room temperature for 20-60 minutes, and then take a certain amount of blank etching solution A for ICP-OES testing of SiO 2 A certain amount of blank etching solution B was taken for ICP-MS testing of the contents of 8 impurity elements.
[0014] Preferably, the PFA vessel is cleaned as follows: 3 After soaking in the solution for at least 2 weeks, wash it with ultrapure water for 6 times, blow it dry with a high-pressure air gun, and test it on the machine to verify that it is qualified as an ultra-clean container for standby use;
[0015] In terms of sampling volume, the sampling volume of blank etching solution A is 1 / 10 of the volume of the HF solution in the ultra-clean container, and the sampling volume of blank etching solution B is 1 / 10 to 1 / 5 of the volume of the HF solution in the ultra-clean container.
[0016] C. Quartz etching solution sampling
[0017] Place the cleaned quartz in a clean PFA container in the sampling area of a Class 100 or above clean room, add the same volume of 4%-10% HF solution as in step B, and place it at room temperature for 20 to 60 minutes. Then take the same volume of quartz etching solution A as blank etching solution A for ICP-OES testing of SiO 2 Content, take the same volume of quartz etching solution B as blank etching solution B and use it to test the contents of 8 impurity elements by ICP-MS;
[0018] D. Measure SiO in etching solution 2 content
[0019] In the sampling area of a Class 100 or above clean room, place the blank etching solution in a clean empty PFA bottle and add an appropriate amount of 0.5% Na 2 CO 3 Solution and ultrapure water, prepare quartz etching solution A in the same way;
[0020] ICP-OES was used to measure the Si content in blank etching solution A and quartz etching solution A respectively. The difference between the two test results was taken and the SiO content in the etching solution was finally calculated by the formula. 2 content and etching depth, the formula is as follows:
[0021] C Si =(C S -C B )*DF*V
[0022]
[0023] Among them, C Si -The silicon content in the etching solution, in mg;
[0024] C S - The concentration of the sample solution calculated from the standard curve, in mg / L;
[0025] C B - Blank solution concentration calculated from the standard curve, in mg / L;
[0026] DF-sample dilution factor;
[0027] V-volume of 4%-10% HF solution used to etch the sample, unit is L;
[0028] C SiO2 -Silicon dioxide content in the sample, in mg;
[0029] d-etched sample depth, in μm,
[0030] ρ-sample density, in g / cm 3 ;
[0031] S - sample surface area, in cm 2 .
[0032] E. Measure the content of 8 impurity elements in the etching solution
[0033] In a clean room of Class 100 or above, place the blank etching solution B in a clean PFA evaporating dish; then heat the PFA evaporating dish on a heating plate at a temperature of 80-120°C. After a certain period of time, when there is no blank etching solution B in the evaporating dish, cool the evaporating dish to room temperature and add an appropriate amount of 0.1-5wt% HNO 3 The solution is the extract, and the extract is recovered after 5-10 minutes. The quartz etching solution B is treated in the same way.
[0034] ICP-MS was used to measure the contents of eight impurity elements in blank etching solution B and quartz etching solution B. The difference between the two test results was taken and the contents of Li, Na, Mg, Al, K, Ca, Cu, and Fe were finally calculated by the formula. The formula is as follows:
[0035]
[0036] Where: C i -Element content in the etching solution, in ng / g;
[0037] C S - The concentration of the sample solution calculated from the standard curve, in ng / L;
[0038] C B - Blank solution concentration calculated from the standard curve, in ng / L;
[0039] DF-sample dilution factor;
[0040] V-volume of 4%-10% HF solution used to etch the sample, unit is L;
[0041] C SiO2 -The amount of silicon in the etching solution, in mg.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) In terms of pretreatment, the present invention fixes the process of quartz cleaning and blank sampling of quartz etching solution in the pretreatment process, reduces the pretreatment etching time, and improves the pretreatment efficiency;
[0044] (2) The etching depth and etching solution SiO can be obtained by using the same quartz etching solution 2 Content and 8 impurity elements content of etching solution;
[0045] (3) Etching solutions at different depths on the quartz surface can be continuously obtained, and the impurity elements in the etching solutions at different depths can be analyzed.
[0046] (4) Enrich the etching solution with impurity elements to avoid the influence of high silicon substrate on the instrument;
[0047] (5) Reduce the elemental impurity content in the enriched etching solution container and lower the detection limit of the method. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 The flow chart of the method for analyzing the element content in the quartz etching solution of the present invention is shown. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solution and advantages of the embodiment of the present invention clearer, the technical solution of the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] The "range" disclosed herein is in the form of a lower limit and an upper limit. It can be one or more lower limits, and one or more upper limits, respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges that can be defined in this way are inclusive and combinable, i.e., any lower limit can be combined with any upper limit to form a range. For example, a range of 100 to 140 and 500 to 900 is listed for a particular parameter, and it is understood that a range of 100 to 140 and 500 to 900 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum ranges 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 2, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5.
[0051] In the present invention, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations.
[0052] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.
[0053] The quartz size in this embodiment is 5 cm in diameter and 0.6 cm in height, and the following steps are included:
[0054] 1. Quartz cleaning:
[0055] Place a clean empty bucket (2-5L) of polytetrafluoroethylene (PTFE) or polyethylene (PE) or polypropylene (PP) in a clean room of Class 100 or above, put quartz in the empty bucket, add pure water, let it stand for 2-5 minutes and then pour it out, repeat the above operation several times. Add 30-100mL of ultrapure water to the PTFE, PE or PP bucket containing quartz, place it in an ultrasonic cleaner, the ultrasonic frequency is 40-80KHz, the ultrasonic cleaning time is 30min, and then rinse with ultrapure water for 1min, repeat the above operation 2-3 times, and finally blow dry with a high-pressure air gun.
[0056] 2. Quartz Etching Blank Solution Sampling
[0057] Place a clean perfluoroalkoxy resin (PFA) container in the sampling area of a Class 100 or above clean room, add 10-50 ml of 4%-10% HF solution, leave it at room temperature for 20-60 minutes, and then take 1-5 ml of blank etching solution A for subsequent ICP-OES testing of SiO 2 Take another 5-10 mL of blank etching solution B for subsequent ICP-MS testing of the contents of 8 impurity elements.
[0058] PFAware with 23% HNO 3 After soaking in the solution for at least 2 weeks, wash it with ultrapure water 6 times, blow it dry with a high-pressure air gun, and test it on the machine to verify that it is qualified before use as an ultra-clean container.
[0059] 3. Quartz etching solution sampling
[0060] Place the cleaned quartz in a clean PFA container in the sampling area of a Class 100 or above clean room, add 10-50 ml of 4%-10% HF solution, leave it at room temperature for 20-60 minutes, and then take 1-5 ml of etching solution A to test SiO by ICP-OES. 2 Take another 5-10 mL of etching solution B and test the contents of 8 impurity elements by ICP-MS.
[0061] 4. Measure SiO in etching solution 2 content
[0062] In the sampling area of a Class 100 or above clean room, take 1-5 mL of blank etching solution A into a clean empty PFA bottle and add an appropriate amount of 0.5% Na 2 CO 3 Solution and ultrapure water were used to prepare quartz etching solution A in the same way. ICP-OES was used to measure the Si content in blank etching solution A and quartz etching solution A. The difference between the two test results was taken and the SiO content in the etching solution was finally calculated by the formula.2 content and etching depth, the formula is as follows:
[0063] C Si =(C S -C B )*DF*V
[0064]
[0065] Among them, C Si -The silicon content in the etching solution, in mg;
[0066] C S - The concentration of the sample solution calculated from the standard curve, in mg / L;
[0067] C B - Blank solution concentration calculated from the standard curve, in mg / L;
[0068] DF-sample dilution factor;
[0069] V-volume of 4%-10% HF solution used to etch the sample, unit is L;
[0070] C SiO2 -Silicon dioxide content in the sample, in mg;
[0071] d-etched sample depth, in μm,
[0072] ρ-sample density, in g / cm 3 ;
[0073] S - sample surface area, in cm 2 .
[0074] The specific results are shown in Table 1:
[0075] Table 1 SiO2, Si content and etching depth results in etching solution
[0076] ICP-OES results result unit Si content 1.3 mg <![CDATA[SiO 2 Element Content]]> 2.8 mg Etching depth 0.26 μm
[0077] 5. Measure the content of 8 impurity elements in etching solution
[0078] In a clean room of Class 100 or above, take 5-10 mL of blank etching solution B and put it in a clean PFA evaporating dish. Heat the PFA evaporating dish on a heating plate at 80-120°C. After a certain period of time, there is no blank etching solution B in the evaporating dish. The evaporating dish is cooled to room temperature and an appropriate amount of 0.1-5wt% HNO is added. 3The solution is the extract, and the extract is recovered after 5-10 minutes, and the quartz etching solution B is prepared in the same way. The contents of 8 impurity elements in the blank etching solution B and the quartz etching solution B are measured by ICP-MS, and the difference between the two test results is taken, and the contents of Li, Na, Mg, Al, K, Ca, Cu, and Fe are finally calculated by the formula, and the formula is as follows:
[0079]
[0080] Where: C i -Element content in the etching solution, in ng / g;
[0081] C S - The concentration of the sample solution calculated from the standard curve, in ng / L;
[0082] C B - Blank solution concentration calculated from the standard curve, in ng / L;
[0083] DF-sample dilution factor;
[0084] V-volume of 4%-10% HF solution used to etch the sample, unit is L;
[0085] C SiO2 -The silicon content of the etching solution in mg.
[0086] The results are shown in Table 2:
[0087] Table 2 Summary of the contents of 8 impurity elements in the etching solution
[0088]
[0089]
[0090] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for analyzing the element content in a quartz etching solution, characterized in that: The steps include: A. Quartz cleaning Place a clean empty bucket in a clean room of Class 100 or above, put the quartz in it, add pure water, let it stand for 2-5 minutes and then pour it out, repeat the above operation several times; then clean it with 40-80KHz ultrasound and blow it dry with a high-pressure air gun; B. Quartz Etching Blank Place a clean perfluoroalkoxy resin PFA container as a super-clean container in the sampling area of a clean room of Class 100 or above, add 4%-10% HF solution, leave it at room temperature for 20-60 minutes, take a certain amount of blank etching solution A for ICP-OES testing of SiO2 content, and take another certain amount of blank etching solution B for ICP-MS testing of 8 impurity element contents; C. Quartz Etching Place the cleaned quartz in a clean PFA container in the sampling area of a clean room of Class 100 or above, add the same volume of 4%-10% HF solution as in step B, and place it at room temperature for a certain period of time, then take the same volume of quartz etching solution A as the blank etching solution A for ICP-OES testing of SiO2 content, and take the same volume of quartz etching solution B as the blank etching solution B for ICP-MS testing of 8 impurity element contents; D. Measure the SiO2 content in the etching solution In the sampling area of a Class 100 or above clean room, place the blank etching solution in a clean empty PFA bottle, add appropriate amounts of 0.5% Na2CO3 solution and ultrapure water, and prepare quartz etching solution A in the same way; ICP-OES was used to measure the Si element content in blank etching solution A and quartz etching solution A respectively. The difference between the two test results was taken and the SiO2 content and etching depth in the etching solution were finally calculated by the formula. The formula is as follows: C Si =(C S -C B )*DF*V Among them, C S i – silicon content in the etching solution, in mg; Cs - sample solution concentration calculated from the standard curve, in mg / L; C B - Blank solution concentration calculated from the standard curve, in mg / L; DF-sample dilution factor; V-volume of 4%-10% HF solution used to etch the sample, unit is L; C S i O2 – The content of silicon dioxide in the sample, in mg; d-etched sample depth, in μm, ρ-sample density, in g / cm 3 ; S - sample surface area, in cm 2 , E. Measure the content of 8 impurity elements in the etching solution In a clean room of Class 100 or above, place blank etching solution B in a clean PFA evaporating dish; then heat the PFA evaporating dish on a heating plate at a temperature of 80-120°C. After a certain period of time, when there is no blank etching solution B in the evaporating dish, cool the evaporating dish to room temperature, add an appropriate amount of 0.1-5wt% HNO3 solution as an extracting solution, and recover the extracting solution after 5-10 minutes; treat quartz etching solution B in the same way. ICP-MS was used to measure the contents of eight impurity elements in blank etching solution B and quartz etching solution B. The difference between the two test results was taken and the contents of Li, Na, Mg, Al, K, Ca, Cu, and Fe were finally calculated by the formula. The formula is as follows: Where: C i -Element content in the etching solution, in ng / g; C S - The concentration of the sample solution calculated from the standard curve, in ng / L; C B - Blank solution concentration calculated from the standard curve, in ng / L; DF-sample dilution factor; V-volume of 4%-10% HF solution used to etch the sample, unit is L; C SiO2 -The amount of silicon dioxide in the etching solution, in mg.
2. The analysis method according to claim 1, characterized in that: in, In step A, the empty barrel is made of a material selected from polytetrafluoroethylene (PTFE), polyethylene (PE) or polypropylene (PP); The ultrasonic cleaning method is as follows: add 1 / 3 to 1 / 2 volume of ultrapure water to the PTFE, PE or PP barrel containing quartz, place it in an ultrasonic cleaner, the ultrasonic frequency is 40 to 80KHz, the ultrasonic cleaning time is 30 minutes, and then rinse with ultrapure water for 1 minute; repeat the above operation 2-3 times, and finally blow dry with a high-pressure air gun.
3. The analysis method according to claim 1, characterized in that: in, In step B, the cleaning method of the PFA vessel is as follows: soak it in 23% HNO3 solution for at least 2 weeks, wash it with ultrapure water for 6 times, blow it dry with a high-pressure air gun, and test it on the machine to verify that it is qualified and then use it as an ultra-clean container for standby use.
4. The analysis method according to claim 1, characterized in that: in, In step B, the sampling volume of the blank etching solution A is 1 / 10 of the volume of the HF solution in the ultra-clean container, and the sampling volume of the blank etching solution B is 1 / 10 to 1 / 5 of the volume of the HF solution in the ultra-clean container.
5. The analysis method according to claim 1, characterized in that: in, In step C, the immersion time of the 4%-10% HF solution is 20-60 minutes.
Citation Information
Patent Citations
Chemical granulation processing method for quartz surface
CN101367618A
Method for simultaneously determining mixed elements in industrially pure iron
CN104777154A
High-purity quartz SiO2 purity and impurity content detection method matched with pretreatment device
CN115718093A
Method for etching surface of quartz crucible
CN118307211A